Extramedullary plasmacytoma in children is a genetically distinct localized neoplasia curable by surgical resection - Ilske Oschlies; Julia Richter; Amelie Alfert; Fernando Chahud; Stephanie Mueller; Ingrid Simonitsch-Klupp; Hannah von Mersi; Andishe Attarbaschi; Karoline Koch; Christoph Schaefers; Monika Brüggemann; Cecilia Bozzetti; et al. (Blood Advances)
Abstract: Extramedullary plasmacytomas (EMPs) are exceedingly rare in children and adolescents. We describe clinical, pathological, and molecular features of 13 patients with EMP in this age group (8 males and 5 females; age 3-18 years). EMPs presented as localized disease involving the Waldeyer’s ring (n = 9), larynx (n = 2), ocular adnexa (n = 1), or epipharynx and conjunctiva simultaneously (n = 1). One patient with EMP of the tonsils had a concurrent Epstein-Barr virus infection. Twelve of 13 patients with follow-up information reached sustained complete remissions after surgical resection (median follow-up, 38 months). However, local relapses were observed in 3 patients. Irradiation was applied in only 1 patient with laryngeal involvement. Histologically, sheets of mature plasma cells with light chain restriction, low proliferation, and predominant expression of immunoglobulin A (11/13 [92%]) were observed. Epstein-Barr virus, CD56, and cyclin D1 were not detected in the plasma cells. Amyloidosis confined to the lesion was observed in 1 case. Clonal, mostly productive immunoglobulin gene rearrangements with somatic hypermutation (3.3%-5.7%) were detectable in all informative cases. Fluorescence in situ hybridization revealed absence of chromosomal abnormalities associated with plasma cell neoplasia (eg, breaks in IGH, MAF, FGFR3, and copy number alterations of 1p32, 1q21, RB1, and TP53). Targeted next-generation sequencing did not reveal any somatic alterations predicted as pathogenic. We conclude that EMP in children and adolescents is a plasma cell neoplasia with low malignant potential lacking systemic dissemination, differing clinically and molecularly from adult plasma cell myeloma.